Bacteriocinogenic Lactococcus lactis subsp. lactis DF04Mi isolated from goat milk: Application in the control of Listeria monocytogenes in fresh Minas-type goat cheese - Furtado,Danielle N. (2015)
Listeria monocytogenes is a pathogen frequently found in dairy products. Its control in fresh cheeses is difficult, due to the psychrotrophic properties and salt tolerance. Bacteriocinogenic lactic acid bacteria (LAB) with proven in vitro antilisterial activity can be an innovative technological approach but their application needs to be evaluated by means of in situ tests. In this study, a novel bacteriocinogenic Lactococcus lactis strain (Lc. lactis DF4Mi), isolated from raw goat milk, was tested for control of growth of L. monocytogenes in artificially contaminated fresh Minas type goat cheese during storage under refrigeration. A bacteriostatic effect was achieved, and counts after 10 days were 3 log lower than in control cheeses with no added LAB. However, this effect did not differ significantly from that obtained with a non-bacteriocinogenic Lc. lactis strain. Addition of nisin (12.5 mg/kg) caused a rapid decrease in the number of viable L. monocytogenes in the cheeses, suggesting that further studies with the purified bacteriocin DF4Mi may open new possibilities for this strain as biopreservative in dairy products.